The Oasis of Bukhara, Volume 1 : Population, Depopulation and Settlement Evolution - Rante, Rocco (Arts and Archaeology of the Islamic World, 2019)
In The Oasis of Bukhara: Population, Depopulation and Settlement Evolution , Rocco Rante, archaeologist at the Louvre Museum, presents the results of a large-scale and ambitious regional archaeological investigation of the oasis of Bukhara, corresponding to the delta of the Zerafshan River, from the end of the 1st millennium BCE to the Timurid period. Rante reports the conclusions of several studies of the oasis, realised with the collaboration of distinguished specialists, and covers topics such as human migration, water and the city, urban development and changes in human behaviour. He also revisits the history of this part of Central Asia, providing new historical and cultural insights arising out of the intense archaeological activities undertaken in the field. The volume is co-published by Brill, Leiden, and the Louvre Museum, Paris.